Production of Writing Paper from a Mixture of Grasses from Andhra Pradesh - Guha, S. R. D.; Dhoundiyal, S. N.; Mathur, G. M.; Sharma, Y. K. (Indian Forester, 1973)
Laboratory and pilot plant scale trials on the production of writing paper from a mixture of grasses from Andbra Pradesb are described. The results indicate that the mixture requires some admixture of long fibre for smooth running of the machine.